Efecto de la inoculación y peletización en la germinación y crecimiento de plantas de maca (Lepidium meyenii W.) a nivel in vitro e invernadero - Vergani, Italo (2018)
Non-pelleted and pelleted seeds of maca (Lepidium meyenii W.) inoculated with three strains (C32, DZ50 and AC7) were compared at in-vitro and greenhouse tests. Percentage of germination and dry weight of plant were measured in-vitro level. Percentage of emergence, root and shoot dry weight were measured in greenhouse. Both germination and emergence percentages were higher in pelleted than non-pelleted treatments. In vitro dry weights of all the pelleted treatments were higher than non-pelleted; pelleted and non-pelleted inoculated dry weights were higher than controls without inoculant. The amount of viable cells and water activity (Aw) of pelleted and non-pelleted seeds were measured; pelleted treatments tend to preserve these two parameters over time.